2015
DOI: 10.1111/jpi.12247
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Melatonin inhibits autophagy and endoplasmic reticulum stress in mice with carbon tetrachloride‐induced fibrosis

Abstract: This study aimed to investigate whether inhibition of autophagy and endoplasmic reticulum (ER stress) associates with the antifibrogenic effect of melatonin in mice treated with carbon tetrachloride (CCl4 ). Mice received CCl4 5 μL/g body wt i.p. twice a week for 4 wk or 6 wk. Melatonin was given at 5 or 10 mg/kg/day i.p, beginning 2 wk after the start of CCl4 administration. Treatment with CCl4 resulted in fibrosis evidenced by the staining of α-smooth muscle actin (α-SMA)-positive cells. CCl4 induced an auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 48 publications
4
76
0
Order By: Relevance
“…In relation to muscle, melatonin is highly versatile molecule and either induces autophagy [86] or inhibits it [87], depending on pathological processes involved, since oxidative stress has a close relationship with autophagy. For example, melatonin induces autophagy in myoblast cells collaborating in myogenic differentiation (MyoD) degradation [88] but it inhibits autophagy in muscles from carbon tetrachloride-treated mice by reducing oxidative stress-induced damage [89]. …”
Section: Cellular Impact Of Sarcopeniamentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to muscle, melatonin is highly versatile molecule and either induces autophagy [86] or inhibits it [87], depending on pathological processes involved, since oxidative stress has a close relationship with autophagy. For example, melatonin induces autophagy in myoblast cells collaborating in myogenic differentiation (MyoD) degradation [88] but it inhibits autophagy in muscles from carbon tetrachloride-treated mice by reducing oxidative stress-induced damage [89]. …”
Section: Cellular Impact Of Sarcopeniamentioning
confidence: 99%
“…Melatonin reduces endoplasmic reticulum stress in skeletal muscle by increasing the expression of several proteins as well as mRNA levels [89]; this improves protein synthesis. Likewise, melatonin is an important regulator of proteasome [94] and lysosomal mechanisms [88], thereby enhancing cell quality.…”
Section: Cellular Impact Of Sarcopeniamentioning
confidence: 99%
“…Recently, increasing studies show ER stress is a salient feature of numerous liver diseases [16,17]. Recently, melatonin is shown to be effective in reducing ER stress-induced hepatic steatosis [18] and tetrachloride-induced liver fibrosis [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Yoo and Jeung showed that melatonin suppresses CsA-mediated autophagy in rat pituitary GH3 cells [18]. San-Miguel et al demonstrated that melatonin inhibits autophagy and endoplasmic reticulum stress in mice with carbon tetrachloride-induced fibrosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of melatonin on autophagy has been investigated more recently [18][19][20]. Yoo and Jeung showed that melatonin suppresses CsA-mediated autophagy in rat pituitary GH3 cells [18].…”
Section: Discussionmentioning
confidence: 99%